Słodko i zaszczytnie..., czyli rzecz o mitologizacji wojny - Baran, Magdalena M. (Civitas. Studia z filozofii polityki, 2018)
Thinking about war is accompanied by associated myths. Some of them act as stimulators for the development of war craft, war-related international law and applied ethics. However, the re are myths that lead to the escalation of a conflict instead of heading faster towards its end. They do not bring a peaceful message, nor do they contribute to building a ‘better state of peace’ after the war has ended. On the contrary, by glorifying sacrifice, they have been shaping the fate of generations for centuries, who directly and personally (voluntarily or under duress) have been engaging in wars. This article is dedicated to one of these dangerous myths, that is dulce et decorum est pro patria mori [how sweet and honourable it is to die for the homeland].